Irritable bowel Syndrome, food intolerance and non- celiac gluten sensitivity. A new clinical challenge - Soares, Rosa Leonôra Salerno; Saad, Maria Auxiliadora Nogueira; Santos, Marcia Maria Sales dos; Souza, Ana Carolina de Azevedo; Lessa, Matheus de Almeida (Seven Editora, 2023)
Approximately 80% of irritable bowel syndrome (IBS) patients report that their symptoms are triggered after ingesting one or specific food groups. Gluten, wheat and related proteins (e.g., amylase-trypsin inhibitors, and fermentable oligo-di-mono-saccharides and polyols (FODMAPs) are the most relevant IBS symptom triggers, although the true ‘culprit(s)’ is/are still not well established. The concept of causal relationship between gluten intake and the occurrence of symptoms in the absence of celiac disease and wheat allergy was termed non-celiac gluten sensitivity (NCGS). The borderline between celiac disease, wheat allergy, IBS and NCGS is not always clearly distinguishable, and the frequency and clinical identity of NGCS are still unclear. An overlap between IBS and NCGS has been detected. The incomplete knowledge of the etiopathogenesis of these clinical conditions, lack of data on their real epidemiology, as well as the absence of a gold standard for their diagnosis, make the overall picture difficult to understand “It is crucial to well define the interaction between IBS, food intolerance and NGCS, since the role of diet in IBS and its dietary management is an essential tool in the treatment of a large number of these patients”. The objective of the present review is to provide an overview highlighting the interaction between IBS, food intolerance and NCGS in order to unravel whether gluten/wheat/FODMAP sensitivity represents ‘facts’ and not ‘fiction’ in IBS symptoms. DOI:https://doi.org/10.56238/ciênciasaudeestuepesv1-074